2014
DOI: 10.1007/s00701-014-2024-x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of titanium cranioplasty—a retrospective analysis of 174 patients

Abstract: In the largest UK study on cranioplasty to date, we have demonstrated that size of defect, traumatic aetiology and bifrontal insertion are risk factors for complications. Our results suggest that the timing of cranioplasty may be important with late (> 12 months) TC associated with a higher rate of complications, although further prospective studies on the optimal timing of TC are required to establish the observed trend. Our data can help clinicians stratify risk to inform the consent process and aid pre-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 25 publications
4
55
1
3
Order By: Relevance
“…6) This data is comparable with several recent studies. 7,8) The exposed implant rate in titanium cranioplasty was recently reported as 13.9% (15 of 108 cases).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…6) This data is comparable with several recent studies. 7,8) The exposed implant rate in titanium cranioplasty was recently reported as 13.9% (15 of 108 cases).…”
Section: Introductionsupporting
confidence: 92%
“…4,5) However, titanium implants may be associated with a significant rate of complications, most commonly infection, and re-operation was sometimes necessary. [6][7][8][9] Exposed implant is an important but less understood complication which can lead to both infection and cosmetic problems.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium is often used in cranioplasty because it is believed to be bioinert and is rigid as well as compatible with magnetic resonance imaging. 3 Although titanium allergy is rare, the possibility of substantial morbidity is real. Death after an acute hypersensitivity reaction to a titanium cranioplasty mesh has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[44] One of the largest retrospective studies on titanium cranioplasties, conducted by Mukherjee et al in London, reported a failure and removal rate of 10.3% and infection rate of 8.6%. [45] When they evaluated reasons for failure, the presence of a previous infection and defect size greater than 100 cm 2 were associated with higher complication rates.…”
Section: Challenges In Cranial Defect Reconstructionmentioning
confidence: 99%